An Analysis of the Biopsychosocial Factors including Sex and Pregnancy in Women with Axial Spondyloarthritis; Data from the Ankylosing Spondylitis Registry of Ireland (ASRI) - Maguire, Sinead Allison (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
With advances in pathophysiology, development of novel classification criteria and the advent of new therapeutic agents the field of axial spondyloarthritis (axSpA) is rapidly evolving. Despite this, the impact and interplay between biopsychosocial factors on patient outcomes in axSpA has received limited attention in the published literature. As a result, there are several subpopulations of patients with axSpA who remain poorly understood and require further evaluation. The aim of this thesis was to characterise the impact of these issues as well as to call attention to their unique challenges and needs in the management of axSpA. To address this aim, a series of studies were designed using cross sectional data from the Ankylosing Spondylitis Registry of Ireland (ASRI). These studies were prefaced by two associated narrative reviews and one systematic review to outline current understanding and current gaps in knowledge.
APPROVED
Keywords: Axial Spondyloarthritis; Spondylitis; Ankylosing Spondylitis